Efficacy of Low Dose Low Molecular Weight Heparin in the Treatment of Cutaneous Lichen Planus (Journal of Armed Forces Medical College, Bangladesh, 2014)
Introduction: Lichen planus is a common pruritic, inflammatory disease of the skin, mucous membranes, nail and hair follicles. Low dose low molecular weight heparin is administered in the treatment of cutaneous lichen planus. Objective: The objective is to evaluate the efficacy of low dose low molecular weight heparin in the treatment of cutaneous lichen planus. Materials and Methods: An interventional study was carried out in the department of Dermatology and Venereology, Combined Military Hospital (CMH), Dhaka. Total thirty seven patients of cutaneous lichen planus were selected by purposive type non-probability sampling technique. Data were collected by face to face interview and clinical examination. Results: It was observed that before treatment, the score of cutaneous lichen planus lesion was 6.83 ± 1.30 and after treatment was 3.83 ± 1.18 and t test was found statistically significant (P